MSWM in Bhopal city: a critical analysis and a roadmap for its sustainable management. Issue 2 (26th April 2018) - Parihar, Rajeev Singh; Ahmed, Sirajuddin; Baredar, Prashant; Sharma, Anil; Ravi Kiran, Tatavarthy
Abstract : The rapid population growth and an increase in the living standard of inhabitants have caused insurmountable problems to the municipal solid waste management (MSWM) of Bhopal city. The city generates approximately 800 t/d of municipal solid waste (MSW) and it is estimated to increase to approximately 2735 t/d by the year 2035. This paper presents an overview of the existing MSWM practices in Bhopal city and suggests a roadmap to overcome the shortcoming. Some of the major drawbacks are: an absence of an engineering landfill, improper management of MSW, lack of suitable facilities (equipment and infrastructure) and funds. This has caused contamination of different environmental slots, including soil, groundwater/surface water and air leading to unhealthy dwelling conditions. Physical and chemical analyses of waste indicates a high concentration (45%) of biodegradable waste, low calorific value (378–4680 kcal/kg) and high moisture content (>30%) of MSW. Overall, 15% of the waste was found suitable for electricity generation. A roadmap for better management is proposed that includes segregation at source, recycling and reuse for sustainable management of MSW as per provisions made in solid waste management rules, 2016. This roadmap will definitely enhance the awareness campaign 'Team Up to Clean Up' launched by Bhopal Municipal Corporation in 2014.